Effect of temperature on 3,4-Methylenedioxypyrovalerone (MDPV)-induced metabolome disruption in primary mouse hepatic cells - Araújo, Ana Margarida (2021)
3,4-Methylenedioxypyrovalerone (MDPV) is one of the most popular cathinone derivatives worldwide and has recently been associated with several intoxications and deaths, in which, similarly to amphetamines, hyperthermia appears to play a prominent role. However, there remains a huge information gap underlying the mechanisms associated with its hepatotoxicity, namely under hyperthermic conditions. Here, we use a sensitive untargeted metabolomic approach based on gas chromatography-mass spectrometry (GC-MS) to investigate the effect of subtoxic and toxic concentrations of MDPV on the metabolic profile of primary mouse hepatocytes (PMH), under normothermic and hyperthermic conditions. For this purpose, hepatocytes were exposed to increasing concentrations of MDPV (LC01, LC10 and LC30) for 24 h, at 37 °C or 40.5 °C, and alterations on both intracellular metabolome and extracellular volatilome were evaluated. Multivariate analysis showed a clear separation between MDPV exposed cells and control cells in normothermic conditions, even at subtoxic concentrations (LC01 and LC10). In normothermia, there was a significant dysregulation of pathways associated with ascorbate metabolism, tricarboxylic acid (TCA) cycle and pyruvate metabolism. These metabolic changes were significantly increased at 40.5 °C, and several other pathways appear to be affected with the evolution of toxicity caused by MDPV under hyperthermic conditions, namely aspartate and glutamate metabolism, phenylalanine and tyrosine biosynthesis, aminoacyl-tRNA biosynthesis, butanoate metabolism, among others. Overall, our findings provide novel insights into the mechanism of hepatotoxicity triggered by MDPV and highlight the higher risks that may occur under hyperthermic conditions.